Effect of the presence of solid particles, on the vanadyl sulfate (VOSO4) oxidation current. (20th March 2021) - Moyeme, C.Y. Sano; Hage, R. El; Hassan, A.; Chauvet, F.; Cassayre, L.; Biscans, B.; Quaranta, D.; Tzedakis, T.
Highlights: VO 2+ electro-oxidation in 'Liquid-Solid' suspensions for vanadium redox batteries. Effect of the stirring of a V (IV) sulphate suspension on the oxidation of the VO 2+ . Influence of inert glass beads on the mass transfer of the VO 2+ in the posolyte. Effect of VOSO4 solid particles on the current of its oxidation. Electronic percolation by ketjen black as an enhancer for the VO 2+ oxidation. Abstract: This study considers the effect of mechanical stirring of V (IV) solutions and of the presence of solid suspensions on the V O ( a q ) 2 + oxidation current measured on a graphite electrode, with the objective of a better understanding of the electrochemical reactions taking place in a vanadium redox flow battery (VRFB). Our research question was to determine whether the presence of different kind of solid particles (inert glass spheres, VOSO4 powder and nanometric ketjen black (KB)) could be beneficial to the electrochemical performances of the VRFB. The experimental method consisted in measuring the anodic limiting current of a VOSO4 -H2 SO4 -H2 O solution on a rotating graphite cylinder, by linear sweep voltammetry. In the absence of solid particles, we show that the mass transfer coefficient dependence against the angular velocity of both the electrode and an additional stirrer obey to a power law ( k   =   f(ω γ )) with an exponent γ found to be lower than the theoretical value. The beneficial effect on the mass transfer of VO 2+ at the interface observed with low fraction of inert glass particles dramatically disappears as the spheres fraction increases. This is attributed to the decrease of the available free volume for the diffusion. When the solid consists of VOSO4 particles, the anodic current decreases as the mass fraction of the solid increases, which demonstrates the absence of any significant beneficial effect of the dissolution of the VOSO4 grains in the diffusion layer. Conversely, an important increase (~ 40%) of the oxidation current is observed when KB particles were introduced at low fractions (0.15%) in the bulk, thanks to the electronic percolation created by the KB. However, this beneficial effect disappears for higher mass fraction of both vanadium or KB solid particles, because of the destruction of the aggregates enabling the electron to be driven into the bulk. Graphical abstract: Image, graphical abstract